Genderwashing in leadership : power, policies and politics - Gardiner, Rita A.; Fox-Kirk, Wendy; Elliott, Carole J.; Stead, Valerie (Transformative women leaders, 2024)
Genderwashing is the process whereby organizational rhetoric differs from the lived experiences of workers, creating the myth of gender equity in the workplace. Genderwashing in Leadership considers how the process of genderwashing highlights hidden biases in organizational policies and procedures, and patriarchal cultural practices. International scholars from diverse areas such as leadership, organizational studies, sociology, and education explore how genderwashing occurs from various perspectives, including leadership, power and privilege, identity, and career recruitment and selection. Uncovering epistemological assumptions that underpin and sustain genderwashing practices, the ways in which genderwashing intersects with embodiment and intersectionality and how genderwashing policies and practices restrict women's advancement into leadership, the editors host a space for dialogue and debate. The Transformative Women Leaders Series is published in collaboration between the International Leadership Association (ILA) and Emerald Publishing. Celebrating women leaders and the leadership styles they employ to achieve success, the books in this series highlight successful context-specific leadership approaches and the moral qualities of endurance.